Phenomenology of Juvenile Delinquency in Society: What Should Parents Do? - Zainal, Zainal; Febriani, Afifah; Oktavia, Gifa; Zahara, Afrila (STIT Ahlussunnah Bukittinggi, 2022)
Juvenile delinquency can be said to be a problem that never ends, as the years go by, the forms and levels of delinquency become more numerous. This is of course still an interesting issue to discuss. In connection with this, this research aims to discuss the forms of efforts made by parents in dealing with juvenile delinquency, as a form of realization of cooperation between parents and the school and the community in overcoming this problem. This research uses a qualitative method with a case study approach. Data sources were taken from parents in Indonesia as key informants, and teenagers as supporting informants through in-depth interviews selected using purposive sampling techniques. The results of the analysis show that the forms of efforts made by parents are: Preventive actions, and efforts to prevent the emergence of juvenile delinquency. Parents make efforts to prevent juvenile delinquency from occurring by strengthening their children's faith, such as ordering them to pray and recite the Koran so that their children always remember Allah SWT. However, their teenage children do not carry it out because they are busy or lazy. Repressive measures, and efforts to crack down on violations of social and moral norms can be carried out by imposing punishments. At this repressive stage, parents only give punishments to children when they are at home. Curative and Rehabilitation Actions: These actions are taken after other preventive measures have been implemented and it is deemed necessary to change the offender's behavior by providing more education. Parents do not provide guidance so that their children do not make the same mistakes.